Selected Abstracts of the 13th International Workshop on Neonatology; Cagliari (Italy); October 25th-28th, 2017 - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 13th International Workshop on Neonatology • The power of Epigenetics • Twins: identical but different • Cagliari (Italy) • October 25th-28th, 2017 ABS 1. NEONATAL ACUTE KIDNEY INJURY AND OXIDATIVE STRESS • A. Babintseva, Y. Hodovanets, L. Agafonova, A. Phrunza ABS 2. LIFE SUPPORT MANAGEMENT IN NEONATES WITH SEVERE OR DISMAL PROGNOSIS: THE OPINIONS OF DOCTORS AND NURSES IN A TERTIARY-LEVEL NEONATAL INTENSIVE CARE UNIT • S. Casarotto, R. Beghini, M. Castellani, E. Bonafiglia, R. Frassoldati, S. Carlassara, F. Carnevale, P. Biban ABS 3. THE METABOLOMICS REVOLUTION IN BRONCHOPULMONARY DYSPLASIA: PERSONAL EXPERIENCE • A. Buffa, M.C. Pintus, M. Lussu, A. Noto, V. Masile, D. Manus, R. Pintus, A. Dessì, V. Fanos, L. Atzori ABS 4. WHARTON'S JELLY: A SIGNIFICANT DETAIL • P. Bini, A. Castiglione, R. Barachetti, G. Rulfi, G. Natalè, E. Villa, M. Barbarini ABS 5. FROM STORK WINGS TO AIRPLANE'S: OUR EXPERIENCE ON 100 NEONATAL TRANSPORTS • F. Ferendeles, C.M. Vacca, D. Frailis, C. Spiga, N. Garau, R. Mazzitti, S. Ibba, A. Cirina, M. Puddu, G. Ottonello, M. Crisafulli, A. Atzei ABS 6. ANOMALIES OF INTRA-HEPATIC BILE DUCT CILIA IN BILIARY ATRESIA • R. Frassetto, F. Parolini, S. Marceddu, G. Satta, T. Pinna, A. Dessanti, V. Villanacci, R. Antonucci, F. Tanda, D. Alberti, K. Schwarz, M.G. Clemente ABS 7. HUMAN HERPES VIRUS 6 INFECTION IN CHILDREN WITH LYMPHOBLASTIC ACUTE LEUKEMIA COMMON: CAUSING AGENT OR CASUAL ASSOCIATION? • F. Marino, S. Rossin, S. Abbate, V. Rametta, S. Innaurato, M. Berardi, F. Rimondi, M. Rotella, S. Zanella, C. Santagati, G. Passarella, F. Rigon, C. Lorenzetto, S. Rugolotto ABS 8. WHOOPING COUGH IN NEWBORN: A CLINICAL CASE DIFFICULT TO SOLVE • M. Vendemmia, G. Parisi, I. Nappa, S. Vendemmia, S. Sciorio ABS 9. FROZEN SECTIONS EXAMINATION OF PLACENTA IN SEPTIC NEWBORNS. THE GENOA EXPERIENCE • M. Paudice, G. Piccardo, A. Allodi, B. Spina, C.M. Biatta, F. Todeschini, F. Buffelli, E. Fulcheri, S. Ferrero, V.G. Vellone ABS 10. THE ACADEMIC PEDIATRICS OF SIENA AND THE GREAT WAR; A STUDY CREATED FOR THE CENTENARY OF THE FIRST WORLD WAR • I. Farnetani, G. Buonocore ABS 11. BRONCHOPULMONARY DYSPLASIA IN A COHORT OF EXTREMELY LOW GESTATIONAL AGE NEWBORNS (ELGANs): 5 YEARS OF EXPERIENCE • V. Masile, D. Manus, M. Puddu, G. Palmas, M.A. Marcialis, F. Bardanzellu, V. Fanos, M.C. Pintus ABS 12. EXTREME THROMBOCYTOSIS IN A PRE-TERM TWIN: A CASE REPORT • S. Becciani, A. Cecchi, C. Dani ABS 13. USE OF PARACETAMOL IN PATENT DUCTUS ARTERIOSUS CLOSURE: THE EXPERIENCE OF THE NEONATAL INTENSIVE CARE UNIT OF CAGLIARI • E. Coni, C. Fanni, M. Testa, G. Palmas, F. Birocchi, F. Cioglia, V. Zurrida, D. Gariel, I. Murgianu, V. Fanos, M. Puddu ABS 14. A CASE OF HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS TRIGGERED BY A CYTOMEGALOVIRUS INFECTION • A. Ferrari, L. Bonetti, V. Del Volgo, M.S. Cosentino, C. Distefano, M. Soliani, R. Delmiglio, F. Comes, A.E. Scaramuzza, C. Cavalli, F. Porta ABS 15. GIOVANNI BUCCI (1928-2016) AND ANTONIO MARINI (1931-2006), LEADING SCHOLARS AND FOUNDING FATHERS OF NEONATOLOGY IN ITALY • L. Cataldi, M.G. Gregorio ABS 16. A FISH... OUT OF WATER • N. Garau, F. Ferendeles, C. Spiga, R. Mazzitti, S. Ibba, A. Cirina, A. Atzei, G. Ottonello ABS 17. ULTRA LATE ONSET DISEASE PRESENTING WITH GROUP B STREPTOCOCCUS MENINGITIS IN A PRETERM TWIN: A CASE REPORT • S. Mastromattei, M.G. Pattumelli, C. Cherchi, A.M. Oggiano, P. Olmeo, L. Abis, R. Antonucci ABS 18. NEONATAL HYPOTONIA: A CASE OF SEVERE CONGENITAL MYOPATHY • A. Mussoni, A. Murianni, A. Atzei, S. Floris, M.E. Trudu, E. Longobardi, A. Manconi, G. Secci, G. Ottonello ABS 19. PERSISTENT FEVER: DO NOT THINK TO EXOTIC DISEASES ONLY, PUT A PROBE ON THE HEART! • G. Passarella, S. Rossin, S. Abbate, V. Rametta, S. Innaurato, M. Berardi, F. Rimondi, M. Rotella, S. Zanella, C. Santagati, F. Marino, F. Rigon, C. Lorenzetto, S. Rugolotto ABS 20. A STRIDOR THAT YOU DON'T EXPECT! • D. Congiu, M. Furno, P. Neroni, G. Ottonello ABS 21. METABOLOMICS OF HUMAN BREAST MILK: PRELIMINARY RESULTS ON THE IMPORTANCE OF SECRETOR PHENOTYPE • G. Pruneddu, F. Cesare Marincola, D.D. Briana, S. Gavrili, S. Georgantzi, A. Dessì, S. Corbu, A. Noto, R. Pintus, V. Fanos, A. Malamitsi-Puchner ABS 22. LONGITUDINAL WEIGHT GAIN FROM BIRTH TO 18-24 MONTHS CORRECTED AGE IN 66 EXTREMELY LOW GESTATIONAL AGE NEWBORNS (ELGANs) WITH AND WITHOUT BRONCHOPULMONARY DYSPLASIA • V. Masile, D. Manus, M. Puddu, G. Palmas, M.A. Marcialis, F. Bardanzellu, V. Fanos, M.C. Pintus ABS 23. A CASE OF SUCCESSFUL PROPRANOLOL TREATMENT OF NEONATAL HEPATIC HEMANGIOMATOSIS • F. Bardanzellu, P. Neroni, C. Ferreli, C. Porcu, E. Longobardi, M.E. Trudu, V. Fanos, G. Ottonello ABS 24. NEONATAL ANTHROPOMETRIC CHARTS FOR TWINS BORN IN ITALY: UPDATE AND COMPARISON • S. Vai, L. De Sanctis ABS 25. BLADDER EXSTROPHY: RECOGNITION AND MANAGEMENT OF A RARE DISEASE • F. Mecarini, C. Fanni, G. Ottonello ABS 26. AMBIGUOUS GENITALIA IN NEWBORN: A CASE REPORT • C. Loddo, C. Fanni, E. Curridori, M. Balzarini, V. Marinelli, A. Reali ABS 27. PEDIATRIC HEADACHE: SIMPLE OR SIMPLY DIFFICULT TO MANAGE? • M.S. Cosentino, V. Del Volgo, C. Distefano, M. Soliani, L. Bonetti, F. Comes, R. Delmiglio, A.E. Scaramuzza, G. Piccini, L. Bianchini, M. Sessa, C. Cavalli, S. Esposito ABS 28. SUBCUTANEUS FAT NECROSIS AND HYPERCALCEMIA: A CLINICAL CASE • M. Vendemmia ABS 29. PHENOTYPIC DISCORDANCE IN DIGEORGE MONOZYGOTIC TWINS • F. Guerra, M. Rossano, G. di Pietro, E. Flore, M. Balzarini, M. Marica, P. Moi ABS 30. FETAL MAGNETIC RESONANCE PARAMETERS IN INTRAUTERIN GROWTH RESTRICTION • S. Perrone, M.G. Alagna, A. Santacroce, I. Paternò, S.F. Carbone, G. Buonocore ABS 31. DRY LUNG SYNDROME AND SEVERE BRONCHOPULMONARY DYSPLASIA WITH FATAL OUTCOME IN TWO PRETERMS OF 29 WEEK'S GESTATION • C. Fanni, C. Loddo, F. Mecarini, M.C. Pintus ABS 32. FETAL MAGNETIC RESONANCE IMAGING APPLICATIONS IN GASTROINTESTINAL CONGENITAL ABNORMALITIES • M. Marras, G. Vivanet, A. Lai, P.P. Bassareo, D. Longo ABS 33. NOT ALL CAUSES OF BAD BREATHING ARE RELATED TO LUNGS • C. Spiga, F. Ferendeles, N. Garau, R. Mazzitti, S. Ibba, A. Cirina, A. Atzei, P. Neroni, M. Puddu, G. Ottonello ABS 34. NEONATAL FEMUR FRACTURE AFTER CAESAREAN SECTION AND BREECH PRESENTATION • S. Rugolotto, P. Friemel, S. Abbate, M. Berardi, S. Innaurato, C. Lorenzetto, F. Marino, G. Passarella, V. Rametta, F. Rigon, F. Rimondi, M. Rotella, C. Santagati, S. Zanella ABS 35. DASH DIET SCORE AND DISTRIBUTION OF BLOOD PRESSURE IN A LARGE COHORT OF SOUTHERN EUROPEAN CHILDREN • P.P. Bassareo, S. Marras, D. Cocco, C. Barbanti, G. Mercuro ABS 36. THE CORRELATIONS BETWEEN THE WIDTH OF THE NEPHROGENIC ZONE AND MATERNAL AND NEONATAL CLINICAL DATA • T. Pilia, A. Dessì, R. Pintus, V. Marinelli, F. Cau, V. Fanos, G. Faa ABS 37. EPSTEIN-BARR VIRUS ENCEPHALITIS: A CASE REPORT • C. Langella, G. Boz, R. Antonucci ABS 38. METABOLOMICS PATHWAYS IN SONS OF MOTHERS WHO ASSUMED NEUROPSYCHOTROPIC DRUGS DURING PREGNANCY: A PILOT STUDY • E. Piga, F. Cesare Marincola, R. Pintus, A. Dessì, V. Fanos, A. Atzei, G. Ottonello ABS 39. PEDIATRIC DIFFERENTIATED THYROID CANCER: EXPERIENCE OF A SINGLE CENTRE IN NAPLES • M. Cacciapuoti, M. Vendemmia, L. Barba, C. Gambale, F. Fonderico ABS 40. GASTRIC PERFORATION IN AN INFANT WITH PATAU SYNDROME: A CASE REPORT • C. Loddo, C. Fanni, V. Zurrida, F. Cioglia, M. Puddu ABS 41. PLEOMORPHIC ADENOMA OF THE SUBMANDIBULAR GLAND: A CASE REPORT IN A CHILD • A. Satta, F. Carta, C. Ripoli, R. Puxeddu, C. Gerosa ABS 42. PRIMARY CONGENITAL HYPOTHYROIDISM IN DISCORDANT TWINS: THE ROLE OF EPIGENETICS. A CASE REPORT • M. Rossano, F. Guerra, F. Pistolesi, G. di Pietro, A. Lampis ABS 43. THE EFFICACY OF VENTED BASE FEEDING BOTTLE IN NEWBORNS: A RANDOMIZED CLINICAL TRIAL. THE ROLE OF A RESEARCH PEDIATRIC NURSE • F. Logrippo, M.C. Ariotti, M. Luciano, E. Maggiora, E. Cocchi, C. Zavattero, A. Coscia, E. Bertino, F. Cresi ABS 44. A CASE OF NORMOCYTIC ANEMIA IN AN INFANT WITH VITAMIN B12 DEFICIENCY • S. Grantaliano, M.G. Pattumelli, M.G. Clemente, C. Locci, R. Antonucci ABS 45. THE CHANGING PATTERN OF HEAD INJURY: REPORT OF TWO CASES • V. Del Volgo, M.S. Cosentino, F. Comes, M. Soliani, C. Distefano, L. Bonetti, R. Delmiglio, A.E. Scaramuzza, G. Piccini, L. Bianchini, C. Cavalli ABS 46. PEMPHIGUS VULGARIS IN CHILDHOOD: A CASE REPORT • A. Manconi, V. Papacciuoli, M.A.